Results 1 to 10 of 10

Math Help - How to simplify this equation?

  1. #1
    Pan
    Pan is offline
    Newbie
    Joined
    May 2008
    Posts
    10

    How to simplify this equation?

    This shouldn't even be difficult for me, but after a good 4 hours and many pages filled, I still cannot get the right answer. I got pretty close, really thought I was going to get it when everything started cancelling, but then my answer is off, although at least the correct format (took me ages to even get that lol, before then I had huge, horribly complex equations that I couldn't simplify).

    This is the equation:
    W=\frac {60(\lambda/60)^2}{(120-\lambda)^2 (1+[\frac {\lambda}{60}]+\frac {1}{2}[\frac {\lambda}{60}]^2\frac {120}{120-\lambda})}

    I need it simplified. The correct answer is:

    W = \frac {\lambda^2}{4-\lambda^2}

    After many hours and pages, I managed to get the following result:

    W = \frac {\lambda^2}{864000-60\lambda^2}

    So, it's at least in the right form, but my \lambda^2 term in the denominator is out by a factor of 15, and the constant term is out by 15*120^2 (I put it like that since 120 appears a lot when solving it).

    I would really appreciate if someone can show me the correct way to simplify this, I have to be able to do this on an exam (revising at the moment).
    Follow Math Help Forum on Facebook and Google+

  2. #2
    Master Of Puppets
    pickslides's Avatar
    Joined
    Sep 2008
    From
    Melbourne
    Posts
    5,236
    Thanks
    29

    Re: How to simplify this equation?

    Post the steps you took.
    Follow Math Help Forum on Facebook and Google+

  3. #3
    Pan
    Pan is offline
    Newbie
    Joined
    May 2008
    Posts
    10

    Re: How to simplify this equation?

    Quote Originally Posted by pickslides View Post
    Post the steps you took.
    OK
    This could take a while
    Follow Math Help Forum on Facebook and Google+

  4. #4
    Pan
    Pan is offline
    Newbie
    Joined
    May 2008
    Posts
    10

    Re: How to simplify this equation?

    \frac {60(\lambda/60)^2}{(120-\lambda)^2 (1+[\frac {\lambda}{60}]+\frac {1}{2}[\frac {\lambda}{60}]^2\frac {120}{120-\lambda})}

    first I simplified the numerator:

    60(\frac {\lambda^2}{3600}) = \frac {\lambda^2}{60}

    then I turned this division by 60 of the numerator into a multiplication by 60 on the denominator:

    \frac {\lambda^2}{(120-\lambda)^2 (60+\lambda+60\frac {1}{2}[\frac {\lambda}{60}]^2\frac {120}{120-\lambda})}

    Simplify that a bit:

    \frac {\lambda^2}{(120-\lambda)^2 (60+\lambda+\frac {\lambda^2}{120}\frac {120}{(120-\lambda)})}

    Those 120s cancel:

    \frac {\lambda^2}{(120-\lambda)^2 (60+\lambda+\frac {\lambda^2}{120-\lambda})}

    I turn (120-\lambda)^2 into (120-\lambda) by multiplying the whole other term by (120-\lambda). This cancels with the last fractional term:

    \frac {\lambda^2}{(120-\lambda) [60(120-\lambda)+\lambda(120-\lambda)+\lambda^2]}

    At this point you can probably see how I got my final answer. I multiplied out the terms in the square brackets, and lots of them cancel:

    \frac {\lambda^2}{(120-\lambda) [7200-60\lambda+120\lambda-\lambda^2+\lambda^2]}

    \frac {\lambda^2}{(120-\lambda) [7200+60\lambda]}

    Then multiply out the two bracket terms:

    \frac {\lambda^2}{864000-60\lambda^2}
    Follow Math Help Forum on Facebook and Google+

  5. #5
    MHF Contributor MarkFL's Avatar
    Joined
    Dec 2011
    From
    St. Augustine, FL.
    Posts
    1,988
    Thanks
    734

    Re: How to simplify this equation?

    I get the same thing you do, and I fed it into the machine and got the same result as well. Are you certain you are beginning with the correct expression?
    Follow Math Help Forum on Facebook and Google+

  6. #6
    Pan
    Pan is offline
    Newbie
    Joined
    May 2008
    Posts
    10

    Re: How to simplify this equation?

    I was pretty sure I was starting with the right thing.

    From the start I have this:

    W=\frac{\mu(\lambda/\mu)^k}{(k-1)!(k\mu-\lambda)^2}p_0

    p_0=\frac {1}{[\sum\limits^{k-1}_{n=0}\frac  {1}{n!}(\frac{\lambda}{\mu})^n]+[\frac{1}{k!} (\frac{\lambda}{\mu})^k  \frac{k\mu}{k\mu-\lambda}]}

    for me k=2 and \mu=60

    therefore

    W=\frac{60(\lambda/60)^2}{1*(120-\lambda)^2}p_0

    and

    p_0=\frac{1}{[1+(\frac{\lambda}{\mu})]+[\frac{1}{2}(\frac{\lambda}{\mu})^2 \frac{2\mu}{2\mu-\lambda}]} = \frac{1}{1+(\frac{\lambda}{60})+\frac{1}{2} (\frac{\lambda}{60})^2 \frac{120}{120-\lambda}}

    so

    W=\frac{60(\lambda/60)^2}{(120-\lambda)^2} \times \frac{1}{1+(\frac{\lambda}{60})+\frac{1}{2} (\frac{\lambda}{60})^2  \frac{120}{120-\lambda}}

    W=\frac{60(\lambda/60)^2}{(120-\lambda)^2 [1+(\frac{\lambda}{60})+\frac{1}{2} (\frac{\lambda}{60})^2   \frac{120}{120-\lambda}]}

    which is where I started in the first post
    Last edited by Pan; January 12th 2012 at 09:09 PM. Reason: more brackets to clarify
    Follow Math Help Forum on Facebook and Google+

  7. #7
    Pan
    Pan is offline
    Newbie
    Joined
    May 2008
    Posts
    10

    Re: How to simplify this equation?

    It is the right answer.

    I was using the wrong \mu. It should have been 1 instead of 60. I was in fact looking at the wrong question entirely!

    Sorry everybody! Doh
    Last edited by Pan; January 12th 2012 at 09:22 PM.
    Follow Math Help Forum on Facebook and Google+

  8. #8
    MHF Contributor MarkFL's Avatar
    Joined
    Dec 2011
    From
    St. Augustine, FL.
    Posts
    1,988
    Thanks
    734

    Re: How to simplify this equation?

    Check p_0; it appears the first term in the denominator should be \frac{1}{60} rather than 1. However, I still do not get the intended result...I get:

    W=\frac{\lambda^2}{(120-\lambda)(119\lambda+120)}
    Follow Math Help Forum on Facebook and Google+

  9. #9
    Pan
    Pan is offline
    Newbie
    Joined
    May 2008
    Posts
    10

    Re: How to simplify this equation?

    Sorry, I have put more brackets in to make that clearer. It wasn't clear what the power was for. When n=0

    \frac{1}{0} (\frac{\lambda}{\mu})^0

    This must be 1 since anything to the power 0 is 1. You are right if the power of n was on the lambda.
    Follow Math Help Forum on Facebook and Google+

  10. #10
    MHF Contributor MarkFL's Avatar
    Joined
    Dec 2011
    From
    St. Augustine, FL.
    Posts
    1,988
    Thanks
    734

    Re: How to simplify this equation?

    Glad you figured it out!
    Follow Math Help Forum on Facebook and Google+

Similar Math Help Forum Discussions

  1. Simplify the below equation
    Posted in the Algebra Forum
    Replies: 3
    Last Post: February 19th 2011, 09:23 AM
  2. Simplify equation - help pls
    Posted in the Algebra Forum
    Replies: 3
    Last Post: December 4th 2010, 07:51 AM
  3. Simplify Equation
    Posted in the Algebra Forum
    Replies: 3
    Last Post: January 30th 2010, 07:09 PM
  4. I cant simplify this equation
    Posted in the Algebra Forum
    Replies: 2
    Last Post: March 23rd 2008, 09:27 PM
  5. Simplify this equation.
    Posted in the Pre-Calculus Forum
    Replies: 5
    Last Post: October 22nd 2007, 03:30 PM

/mathhelpforum @mathhelpforum